Study of the ionisation in a nickel plasma by Inductively Coupled Impulse Sputtering (ICIS) - Loch, Daniel A.L.; Ehiasarian, Arutiun P. (International Conference on Plasma Surface Engineering, 2013)
Inductively coupled impulse sputtering (ICIS) removes the need for a magnetron, while delivering equal or higher ion to neutral ratios compared to other ionised PVD technologies such as high power impulse magnetron sputtering (HIPIMS). This is especially advantageous for the sputtering of magnetic materials, as these would shunt the magnetic field of the magnetron, thus reducing the efficiency of the sputtering and ionisation process. ICIS produces highly ionised metal-dominated plasmas inside a high power pulsed RF coil with a magnet free high voltage pulsed DC powered cathode. ICIS processing with Ti and Cu has been attempted before; however operation with magnetic target materials has not been attempted so far. The paper aims to clarify the effects of power and pressure on the deposition flux and structure of deposited Ni films. The setup comprises of a 13.56 MHz pulsed RF coil operating at a frequency of 500 Hz and a pulse width of 150 µs, which results in a duty cycle of 7.5 % . A pulsed DC voltage of 1900 V was applied to the cathode to attract Argon ions and initiate sputtering. Optical emission spectra (OES) for argon and nickel species sputtered at a constant pressure of 14 Pa, show a linear intensity increase for peak RF powers of 1000 W - 4800 W. Ni neutral line intensity increased linearly exhibiting two different slopes for powers below 2000 W and those above 2000 W RF - power. The influence of pressure on the process was studied at a constant peak RF power of 3000 W for pressures of 3.2 – 26 Pa. The intensity of nickel neutrals rises linearly for pressures of 3.2- 26 Pa and saturates for pressures from 12 – 21.4 Pa. Argon neutrals rise linearly with increasing pressure. Ni ions have not been visible in the OES spectra and analysis into the ion to neutral ratios will be conducted by other techniques. From the Ti process we know, that the intensity of neutrals and ions increases linearly with power and pressure. Intensity modelling is also conducted for the Ni process. The deposition rate for Ni is 50 nmh-1 for a RF-power of 3000 W and a pressure of 14 Pa. The microstructure of the Ni coatings shows columnar dendritic growth. Bottom coverage of unbiased vias with width 0.300 µm and aspect ratio of 3.3:1 was 15 % and for an aspect ratio of 1.5:1 was 47.5 %. Parameters for this coating are mean values from a power and pressure matrix. To investigate ionisation influence, coatings have also been deposited at higher power and pressure. The current work has shown that the concept of combining a RF powered coil with a magnet-free pulsed DC powered cathode works very well for the sputtering of hard magnetic material in very stable plasma.